Pengaruh Motivasi Belajar Terhadap Prestasi Akademik Siswa (Studi Kasus di Kelas 7 dan 8 SMP Swasta Bandung, Medan Tembung) - Alamsyahdana, Azwar; Sani, Dinda Aulia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this research to know, the influence of study motivation through students’ study achievement in student.The problem in this researh is there any inflvence the students study metivation through the students study achievement. Research used method quantitative. which consist of 119 students. Sample were 60 students using simple random sampling. Result there influence students’ study motivation through students study achievement. Correlation between students study motivation index with study achievement used simple linier regression is vR=0,610 was vF=75,3% to vY. It was indicated that 24,7% influenced by other factors. conclusion in this research is there was an influence of study motivation through students study achievement.